Antiepileptic drugs and the risk of ischaemic stroke and myocardial infarction: a population-based cohort study. Issue 8 (12th August 2015) - Renoux, Christel; Dell'Aniello, Sophie; Saarela, Olli; Filion, Kristian B; Boivin, Jean-François
Abstract : Objectives: Hepatic enzyme-inducing antiepileptic drugs (AEDs) increase serum lipid levels and other atherogenic markers via the induction of cytochrome P450 and may therefore increase the risk of vascular events. We sought to assess the risk of ischaemic stroke and myocardial infarction (MI) according to AED enzymatic properties. Design: Population-based cohort study with nested case–control analysis. Setting: 650 general practices in the UK contributing to the Clinical Practice Research Datalink. Participants: A cohort of 252 407 incident AED users aged 18 or older between January 1990 and April 2013. For each case of ischaemic stroke or MI, up to 10 controls were randomly selected among the cohort members in the risk sets defined by the case and matched on age, sex, indication for AED, calendar time and duration of follow-up. Interventions: Current use of enzyme-inducing and enzyme-inhibiting AEDs compared with non-inducing AEDs. Primary outcome measures: Incidence rate ratios (RRs) of ischaemic stroke and MI. Results: 5069 strokes and 3636 MIs were identified during follow-up. Inducing AEDs use was associated with a small increased risk of ischaemic stroke (RR=1.16, 95% CI 1.02 to 1.33) relative to non-inducing AEDs, most likely due to residual confounding. However, current use of inducing AEDs for ≥24 months was associated with a 46% increased risk of MI (RR=1.46, 95% CI 1.15 to 1.85) compared with the same duration of non-inducing AED, corresponding to a risk difference of 1.39/1000 (95% CI 0.33 to 2.45) persons per year. Current use of inhibiting AED was associated with a decreased risk of MI (RR=0.81, 95% CI 0.66 to 1.00). Conclusions: The use of enzyme-inducing AEDs was not associated with an increased risk of ischaemic stroke; a small increase of MI with prolonged use was observed. In contrast, use of inhibiting AEDs was associated with a decreased risk of MI.